2018
DOI: 10.1186/s12876-018-0830-y
|View full text |Cite
|
Sign up to set email alerts
|

Expanding laparoscopic pancreaticoduodenectomy to pancreatic-head and periampullary malignancy: major findings based on systematic review and meta-analysis

Abstract: BackgroundLaparoscopic pancreaticoduodenectomy (LPD) remains to be established as a safe and effective alternative to open pancreaticoduodenectomy (OPD) for pancreatic-head and periampullary malignancy. The purpose of this meta-analysis was to compare LPD with OPD for these malignancies regarding short-term surgical and long-term survival outcomes.MethodsA literature search was conducted before March 2018 to identify comparative studies in regard to outcomes of both LPD and OPD for the treatment of pancreatic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
(79 reference statements)
5
34
0
Order By: Relevance
“…Perioperative outcomes showed that there were differences in the operation time in the non-corrected data and PSM data. This result suggests that regardless of disease severity, MIPD is a more lengthy procedure because of technical difficulties; this result is also similar to the findings of previous reports [14,23,29,30]. However, despite the longer operation time of MIPD, overall complication and in-hospital / late complication rates did not differ between the two groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Perioperative outcomes showed that there were differences in the operation time in the non-corrected data and PSM data. This result suggests that regardless of disease severity, MIPD is a more lengthy procedure because of technical difficulties; this result is also similar to the findings of previous reports [14,23,29,30]. However, despite the longer operation time of MIPD, overall complication and in-hospital / late complication rates did not differ between the two groups.…”
Section: Discussionsupporting
confidence: 89%
“…The development of MIPD was based on Gagner and Pomp's original LPD description from 1994 [22]. Several studies from high-volume centers have reported that MIPD might be feasible and confer advantages over OPD for benign lesions and periampullary malignancy [23][24][25]. However, reservations concerning the safety of MIPD persist as the majority of hospitals performing MIPD were low-volume centers, and its use has been associated with increased morbidity and mortality [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical indications for Lap PD may be similar to those for Open PD . Benign and low‐grade malignant (borderline malignant) periampullary tumors are the best indications for Lap PD when considering long‐term survival and quality of life, as minimal or no lymphadenectomy is needed .…”
Section: Indications For Lap‐pdmentioning
confidence: 99%
“…Intraoperatively, wise decision‐making for open conversion to laparotomy is paramount. For patient safety, failure to progress within 1 hour of dissection as a result of severe pancreatitis or adhesions, unexpected vascular invasion, unexpected adjacent organ involvement requiring combined organ resection, unusual vascular anatomy, and uncontrolled bleeding may warrant open conversion to laparotomy . Although combined segmental resection of the major venous system is feasible and safe, only expert surgeons can carry out this difficult intraoperative situation to complete a safe and successful Lap PD.…”
Section: Indications For Lap‐pdmentioning
confidence: 99%
“…Apart from distal pancreatectomy and enucleation, minimally invasive pancreatic surgery, including robot-assisted surgery, has not yet gained widespread acceptance in the surgical community around the world. It is associated with reduced morbidity, enhanced postoperative recovery, and shorter hospital stay [2,3,4]; however, recent studies also found that its widespread use can also increase morbidity and mortality [5]. Thus, more widespread use of minimally invasive pancreatoduodenectomy requires structured training programs.…”
Section: Introductionmentioning
confidence: 99%